Through-and-Through Suture Technique to Stabilize a Sheath in Branched Endovascular Aortic Repair. (December 2019) - Panuccio, Giuseppe; Rohlffs, Fiona; Makaloski, Vladimir; Eleshra, Ahmed; Tsilimparis, Nikolaos; Kölbel, Tilo
Purpose: To describe a technique to catheterize antegrade branches of a branched thoracoabdominal endograft from a femoral access with the help of standard sheaths and a vascular suture.Technique: The technique is demonstrated in a patient who underwent successful complex thoracoabdominal branched endovascular aortic repair. After the deployment of an aortic endograft with two antegrade branches for the targeted renovisceral vessels, a standard braided sheath was preloaded with a 3/0 polypropylene suture and introduced inside an additional sheath from the groin to the thoracic aorta. Simultaneous gentle traction on the suture as the preloaded sheath was advanced achieved a very stable 180° curve of the proximal end of the sheath. It was possible to selectively catheterize the antegrade branches and respective target vessels sequentially, as well as deploy the planned bridging stents for each branch.Conclusion: The through-and-through suture technique is a helpful tool in branched endovascular aortic repair. It saves time, radiation, and materials; no snare is needed, and it can be preloaded into a sheath.